The cross-sectional association between lifestyle behaviors and breast and cervical cancer screening among Hispanic women along the Texas-Mexico border - Paul Gerardo Yeh; Audrey C. Choh; Susan P. Fisher-Hoch; Joseph B. McCormick; David R. Lairson; Belinda M. Reininger (Preventive Medicine Reports)
Objective: Lifestyle behaviors may influence timely cancer screening, but their relationship is unknown among Hispanic women who have low cancer screening rates. Methods: We used Cameron County Hispanic Cohort data from 2014 to 2022 to evaluate the relationship between lifestyle and compliance with mammography and Papanicolaou (Pap) screening guidelines (“up-to-date”) among Hispanic women along the Texas-Mexico border. The 2018 World Cancer Research Fund scoring system characterized cancer-preventive lifestyle adherence. Multivariable logistic regression assessed the association between lifestyle behaviors and mammography and, separately, Pap screening. Results: Among 385 age-eligible women for mammography and 412 age-eligible women for Pap test screening, up-to-date mammography and Pap screening were seen in 66.7 % (95 % CI: 58.8–73.7 %) and 71.4 % (95 % CI: 63.6–78.0 %) of women, respectively. Compared to non-adherence, adherence to waist circumference (AOR adjusted odds ratio 9.1, 95 % CI: 1.1–77.9; P = 0.04) and alcohol guidelines (AOR 9.4, 95 % CI: 1.1–81.6; P = 0.04) were associated with up-to-date mammography. Consumption guideline adherence to fruit and vegetable (AOR 4.0, 95 % CI: 1.2–13.4; P = 0.03), ultra-processed foods (AOR 7.5, 95 % CI: 1.6–34.7; P = 0.01), red meat (AOR 6.8, 95 % CI: 1.3–34.8; P = 0.02), and sugary beverages (AOR 16.9, 95 % CI: 2.1–138.4; P = 0.01) were associated with up-to-date Pap screening. Conclusions: Differential factors were associated with increased odds of being up-to-date with mammography versus Pap test screening. Lifestyle behavior promotion complements cancer prevention interventions. Contextual insight into the association between lifestyle and cancer screening provides a foundation for future endeavors to augment these two core components of cancer prevention to address Hispanic women's rising breast and cervical cancer risk.